Clinical relevance of SCN and CyN induced by ELANE mutations: a systematic review - Xiao, Yufan; Wang, Nandi; Jin, Xinghao; Liu, Anna; Zhang, Zhiyong (Frontiers in Immunology, 2024)
According to the PRISMA criteria, a systematic review has been conducted to investigate the clinical relevance between patients with severe congenital neutropenia(SCN) and cyclic congenital neutropenia (CyN) induced by ELANE mutations. We have searched PubMed, EMBASE, Web of Science, Scopus, Cochrane, CNKI, Wanfang Medicine, and VIP for ELANE mutation related literature published from 1997 to 2022. Using Microsoft Excel collect and organize data, SPSS 25, GraphPad Prism 8.0.1, and Omap analyze and plot statistical. Compare the gender, age, geography, mutation sites, infection characteristics, treatment, and other factors of SCN and CyN patients induced by ELANE mutations, with a focus on exploring the relationship between genotype and clinical characteristics, genotype and prognosis. This study has included a total of 467 patients with SCN and 90 patients with CyN. The onset age of SCN and CyN are both less than 1 year old, and the onset and diagnosis age of SCN are both younger than CyN. The mutation of ELANE gene is mainly missense mutation, and hot spot mutations include S126L, P139L, G214R, c.597+1G>A. The highfrequency mutations with severe outcomes are A57V, L121H, L121P, c.597+1G>A, c.597+1G>T, S126L, C151Y, C151S, G214R, C223X. Respiratory tract, skin and mucosa are the most common infection sites, Staphylococcus Aureus, Pseudomonas Aeruginosa and Escherichia Coli are the most common pathogens. Patients with refractory G-CSF are more likely to develop severe outcomes. The commonly used pre-treatment schemes for transplantation are Bu-Cy-ATG and Flu-Bu-ATG. The prognosis of transplantation is mostly good, but the risk of GVHD is high.